Enhancing Feasibility Studies for Micro, Small, and Medium Enterprises During the COVID-19 Pandemic - Abiprayu, Kris Brantas; Amal, Muhammad Ihlashul’; Prihandono, Dorojatun (Indonesian Journal of Devotion and Empowerment, 2023)
Pandemi Covid-19 telah berlangsung lebih dari satu tahun dan telah berdampak besadi berbagai sektor kehidupan, tidak terkecuali sektor ekonomi. Hampir semua usaha di semua tingkatan skala bisnis terdampak termasuk usaha mikro kecil dan menengah (UMKM). Sebagai contoh, Kota Tegal yang memiliki klaster-klaster UMKM unggulan juga terdampak. Tim pengabdian melaksanakan pengabdian dengan mitra pelaku UMKM di Kota Tegal dengan judul “Workshop Studi Kelayakan Usaha Mikro Kecil Dan Menengah di Masa Pandemi COVID 19”. Pelaksanaan pengabdian akan dilakukan dengan metode ceramah, tanya jawab, diskusi, simulasi, dan pendampingan. Beberapa materi yang akan diberikan tidak hanya peluang bisnis di masa Pandemi Covid-19 tetapi juga mempertimbangkan permasalahan UMKM yang melekat sampai dengan saat ini seperti strategi bisnis, kelayakan usaha, pembukuan, tata kelola kas, arus kas dan investasi. The Covid-19 pandemic has been ongoing for more than a year and has significantly impacted various sectors of life, including the economic sector. Almost all businesses at all levels of the business scale have been affected, including micro, small, and medium enterprises (MSMEs). For example, the city of Tegal, which has clusters of prominent MSMEs, has also been affected. The community engagement team conducted an engagement with MSME actors in the city of Tegal under the title 'WORKSHOP ON FEASIBILITY STUDY OF MICRO, SMALL, AND MEDIUM ENTERPRISES DURING THE COVID-19 PANDEMIC.' The engagement activities will be conducted using methods such as lectures, question and answer sessions, discussions, simulations, and mentoring. Some of the topics that will be covered include not only business opportunities during the Covid-19 pandemic, but also consider the ongoing issues faced by MSMEs, such as business strategies, feasibility, bookkeeping, cash management, cash flow, and investment.